1986
DOI: 10.1007/bf00123214
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoglucoisomerase variation in Trifolium repens

Abstract: An electrophoretic survey carried out at the PGI/2 locus of white clover revealed the existence of five alleles. These alleles were shown to be controlled by single co-dominant genes, behaving in a normal Mendelian manner. The results also indicate that white clover behaves as an amphidiploid, in which one of its parental species is normally homozygous for the 'c' allele at the PGI/2 locus, whilst the other parent has a multi-allelic series at this locus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

1989
1989
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
1
5
1
Order By: Relevance
“…repens (Michaelson-Yeates, 1986) identified five alleles (a,b,c,d,f) controlled by a single codominant gene that behaved in a normal Mendelian manner. These alleles gave rise to ten different banding patterns and because of gene dosage, genotypes containing different proportions of the same allele could be distinguished.…”
Section: Results Lsoenzyme Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…repens (Michaelson-Yeates, 1986) identified five alleles (a,b,c,d,f) controlled by a single codominant gene that behaved in a normal Mendelian manner. These alleles gave rise to ten different banding patterns and because of gene dosage, genotypes containing different proportions of the same allele could be distinguished.…”
Section: Results Lsoenzyme Analysismentioning
confidence: 99%
“…A number of research workers have suggested that C nigrescens may be one of the possible ancestors of T. repens (Brewbaker & Keim, 1953;Hovin, 1962). A survey at the PGI/2 locus of T. repens strongly suggested that C repens behaves as an amphidiploid in which one of its genomes expresses a multiallelic series whilst the other is homozygous for the c allele (Michaelson-Yeates, 1986). The results of the PGI/2 survey in this paper revealed that, out of the five alleles found in C repens, the only one that could be identified with a band in T. nigrescens was the c allele.…”
Section: Discussionmentioning
confidence: 99%
“…Each of the isoloci apparently have a frequent allele, e.g., the allele p is estimated to have a frequency of 0.60 at the first isolocus. MICHAELSON-YEATES (1986), studying Pgi segregation in white clover cultivars, found that only one of the ancestral genomes had a multi-allelic series whilst the other was homozygous. In contrast, I find that the two most common alleles occur in both of the Pgi isoloci in the population studied (WEIDEMA 1995), just as is the case for Zdh.…”
Section: Discussionmentioning
confidence: 99%
“…The study by ENNOS (1982) provides data on an esterase locus where the alleles segregate as for a diploid. Further studies of T. repens cultivars have, however, provided segregation patterns indicative of polyploid, disomic inheritance ( MICHAELSON-YEATES 1986;PRINS et al 1989;SAWADA and YAMAUCHI 1994;MARSHALL et al 1995). It is important to clarify the inheritance patterns of this polyploid species since the subsequent methodology and treatment in studies on breeding system, population structure and gene flow depend on this.…”
mentioning
confidence: 99%
“…Michaelson-Yeates (1986) investigated the PGI enzyme system in white clover. Forty-five families were investigated and five alleles (A, B, C, D, and F) were found at the PGI-2Iocus.…”
Section: Introductionmentioning
confidence: 99%